ANTIOXIDANT ACTIVITY TEST AND ANALYSIS OF COMPOUNDS CONTAINED IN ANGELS’S TRUMPET FLOWER EXTRACT (Brugmansia suaveolens) - Wuwungan, Axel; Manampiring, Nonny; Gedoan, Sukmarayu; Mokosuli, Yermia Semuel; Roring, Verawati Ida Yani (Universitas Negeri Manado, 2025)
Indonesia is a highly biodiverse country, second only to Brazil. This gives Indonesia enormous potential in ethnopharmacology. Previous studies have shown that the leaves of the Brugmansia suaveolens plant, also known as Angel trumpet, have high antioxidant activity. The aim of this study is to test the antioxidant activity of B. suaveolens flowers and conduct quantitative screening to determine which compounds play the greatest role in their antioxidant activity. This research used the DPPH test and Gas Chromatography-Mass Spectrometry (GC-MS) screening. Ascorbic acid was used as the comparator in this study. Before the DPPH and GC-MS testing, the samples were extracted using the cold maceration technique with a 95% ethanol solvent. Then, the samples were concentrated using a rotary evaporator. The IC₅₀ value of the ethanol extract of B. suaveolens flowers is 196.16 µg/mL, while the IC₅₀ value of ascorbic acid, the comparator, is 3,814 µg/mL. This result shows that the ethanol extract of B. suaveolens flowers has moderate antioxidant activity. Screening bioactive compounds with GC-MS showed that Hexadecenoic acid and Octadecanoic acid play the biggest role in antioxidant activity. However, the compound with the highest content in the ethanol extract of B. suaveolens flowers is scopolamine.